Hate Language as a Negative Phenomenon of the Ukrainian Domestic Media Space in News Content about the War - Shulska, Nataliia; Kostusiak, Nataliia; Zyma, Olha; Larina, Kateryna; Bukina, Nataliia; Kevliuk, Iryna; Ostapchuk, Svitlana (My University, 2023)
The article presents an analysis of hate speech in news content about the war. The study was conducted on the basis of the materials of Ukrainian domestic mass media (regional and all-Ukrainian). The negative impact of this phenomenon in the conditions of the Russian-Ukrainian war is indicated (it leads to the division of society, conflicts between separate groups of citizens, demoralization of Ukrainians, discrediting of one in the eyes of others). Those social groups of people, which are subject to heat speech in journalistic materials the most are differentiated (internally displaced persons, Russian-speaking Ukrainians). The reasons for the spread of hate rhetoric in the headline complex of the studied texts were revealed: clickbait, sensationalism, ignorance of the topic of the material. The analysis of manifestations of hate speech in the Ukrainian mass media was carried out on the basis of monitoring the news of regional and of all-Ukrainian mass media, conducted by the Institute of Mass Information, “Media Detector”. In the research, we also use the advice of leading media experts investigating the topic of hate rhetoric. It was found that manifestations of hate speech are the dissemination of information in any form that contains hostile attitudes, intolerance, disgust, offensive or derogatory comparisons. The rhetoric of hate speech contributes to the development of social stereotypes, forms prejudice and generates discrimination. After the full-scale invasion, a large number of Russian negative ‘messages’ entered the Ukrainian media space, trying to sow hatred, divide society, and discredit some Ukrainians in the eyes of others. Under this influence, negative statements penetrate the domestic mass media, often spontaneously, testifying to manifestations of “hate speech”. Emphasis is placed on the incorrect use by the Western Ukrainian mass media of the terms refugees instead of normative ones displaced persons, internally displaced persons, and temporarily displaced persons. Generalization and stereotyping in the depiction of internally displaced persons (IDPs) in criminal materials, Russian-speaking citizens in the context of war, which gives rise to hate rhetoric in publications, is noted. It has been revealed that changes in the use of language tools caused by the full-scale Russian invasion of Ukraine are also reflected in the textual culture of journalistic publications. At the same time, the choice of stylistically colored vocabulary should take into account the genre of the material, the topic and the audience. Recommendations are also provided for tolerance in the media sphere and avoiding negative statements that help the enemy promote false narratives.
Keywords: hate speech; news; war; Ukrainian mass media; correct vocabulary